2021
DOI: 10.3390/ijerph182111696
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders in Cancer—A Systematic Review

Abstract: Introduction: Sleep disorders, especially insomnia, are very common in different kinds of cancers, but their prevalence and incidence are not well-known. Disturbed sleep in cancer is caused by different reasons and usually appears as a comorbid disorder to different somatic and psychiatric diagnoses, psychological disturbances and treatment methods. There can be many different predictors for sleep disturbances in these vulnerable groups, such as pre-existing sleep disorders, caused by the mental status in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 88 publications
2
40
0
Order By: Relevance
“…21 We found a moderately higher risk in the first-and second-generation immigrant studies in males and females being Swedish-born or native Swedish females, as well as among second-generation immigrant females. We also found cancers to be associated with narcolepsy in some groups in accordance with a review, 22 possibly owing to the chance that narcolepsy was more easily detected in these individuals. We also included preterm birth as a co-factor in the second-generation study, but this did not change the HRs other than marginally.…”
Section: The Association Between the H1n1 Influenza And Narcolepsy Insupporting
confidence: 87%
“…21 We found a moderately higher risk in the first-and second-generation immigrant studies in males and females being Swedish-born or native Swedish females, as well as among second-generation immigrant females. We also found cancers to be associated with narcolepsy in some groups in accordance with a review, 22 possibly owing to the chance that narcolepsy was more easily detected in these individuals. We also included preterm birth as a co-factor in the second-generation study, but this did not change the HRs other than marginally.…”
Section: The Association Between the H1n1 Influenza And Narcolepsy Insupporting
confidence: 87%
“…It is estimated that 30% to 50% of patients with cancer have severe sleep difficulties, such as insomnia, 11 and recent randomized controlled trials have suggested a small to moderate effect of aerobic exercise or resistance exercise on sleep quality in these patients. [12][13][14] There is a well-documented benefit of exercise on sleep outcomes in other patient populations as well.…”
Section: Review Of Exercise Oncology Evidencementioning
confidence: 99%
“…These signs are frequently misdiagnosed as a lingering cold or an ongoing mouth sore. Other signs of oral cancer may include: • Sore on lip or mouth that won't heal • Jaw discomfort or stiffness • Pain in tongue [30][31][32][33] Cancer screening, early detection Numerous traditional diagnostic methods are frequently employed to find oral cancer. Early cancer detection allows for more effective treatment.…”
Section: Common Oral Cancer Symptomsmentioning
confidence: 99%